(untitled) (ARQUISUR Revista, 2019)
An imaginary journey begins from the manuscript book La ciudad sin nombre by Joaquín Torres García, published in Montevideo in 1941, and the text is analyzed focusing on the city cartographies that emerge from it. The words and paragraphs, as well as the fragments of the city drawn in the book, exhibit an atomized world, whose unitary reading is only possible through a fragmented and juxtaposed vision. The constructivist temporality, the spatiality and geometry, the urban micro–landscapes of the port and the bar are analyzed; the nocturnal environment and the human landscape of the city. The trip ends at the symbolic fountain or Cosmic Monument, built in the Rodó Park of the city of Montevideo and drawn on the final page of the manuscript book. Reflections are established on its materiality and location, as well as its symbolic condition. Finally, reference is made to the Uruguayan cultural and literary context in the 40s, in a system of relationships that helps to tell the context of this imaginary trip.